Edukasi PHBS Untuk Pencegahan Demam Berdarah Dengue ( DBD) Pada Ibu PKK RT 004, Labuhan Ratu, Bandar Lampung - Emantis Rosa; Yulianti; Enur Azizah; Linda Septiani (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The development of dengue cases that tend to increase from year to year requires efforts to prevent and control the vector to reduce the vector population. One of them is through Clean and Healthy Living Behavior (PHBS) in the community. PHBS is an awareness movement to get used to clean and healthy living behavior in everyday life, which aims to change people's behavior so that they are more aware, willing and able to perform clean and healthy living actions so that they can improve the quality of public health, especially in vector control. PHBS for the prevention of dengue is more focused on the eradication of Aedes aegypti mosquito nests through the 3M Plus program, namely: keeping the environment clean, and protecting oneself from mosquito bites. The results of the PHBS counseling activities for the prevention of Dengue Hemorrhagic Fever (DHF) in mothers of PKK RT 004, Labuhan Ratu, Bandar Lampung from the evaluation results of an increase in understanding from the participants for a score of 80 8.33% (2 people), during the pre-test it increased to 62.5% (15 people) after the post-test an increase of 54,2 %, meaning that the number of participants with low scores decreased after the presentation of the material. In general, this devotional activity has a positive impact on the retention of mothers of participants in the handling of dengue fever through PHBS.